DESKRIPSI KEMAMPUAN PENALARAN MATEMATIS DAN KEMAMPUAN LITERASI MATEMATIS SISWA KELAS XII DALAM MENYELESAIKAN SOAL CERITA MATEMATIKA - Nurmalita Arisca; Bambang Sri Anggoro; Novian Riskiana Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematical reasoning and literacy are essential for solving word problems. However, students still face difficulties because solving word problems requires not only numeracy skills but also the ability to understand information, analyze solution steps, and draw conclusions. This qualitative descriptive study aims to describe students’ mathematical reasoning and literacy skills in solving word problems. The study involved 12 students from classes XII F-5 and XII F-6 selected through purposive sampling, consisting of two students in each category: high, medium, and low reasoning and literacy abilities. Data were collected through tests, interviews, and documentation, and analyzed using data reduction, data presentation, and conclusion drawing. The results showed that mathematical reasoning abilities in class XII F-5 were 9% high, 28% medium, and 63% low, while in class XII F-6, they were 27% high, 21% medium, and 52% low, indicating overall low reasoning skills. Meanwhile, mathematical literacy abilities in class XII F-5 were 22% high, 62% medium, and 16% low, and in class XII F-6, 15% high, 67% medium, and 18% low, indicating overall medium literacy skills.